A new proposal for evaluating of the solubility of bioceramic materials in dentin tubes after immersion in PBS: a laboratory investigation - Mendonça, Giovanna da Cunha [UNESP]; Tavares, Karina Ines Medina Carita [UNESP]; Santos-Junior, Airton Oliveira [UNESP]; Pinto, Jáder Camilo; Guerreiro-Tanomaru, Juliane Maria [UNESP]; Tanomaru-Filho, Mário [UNESP] (FapUNIFESP (SciELO), 2023)
Introduction: Repair materials must have low solubility. Phosphate buffered saline (PBS) allows simulating clinical condition and interaction with dentin may be important for the correct evaluate of mass loss of bioceramic cements. Objective: To evaluate the effect of distilled water (DW), or PBS immersion on the solubility of Bio-C Repair (BCR, Angelus) or MTA Repair HP (MTAHP, Angelus) using a dentin tube model. Material and method: Bovine dentin tubes with a length of 4 mm, an internal diameter of 1.5 mm and walls thickness of approximately 1 mm were made. The specimens were immersed in DW for 24h, then filled with BCR or MTAHP (n = 14) and stored in an oven at 37°C and 95% humidity for 24h. After being weighed on a precision balance to determine the initial mass, the specimens were immersed in DW (pH 6.5) or PBS (pH 7.0) (n = 7) for 28 days. Empty tubes also were used for calculating the mass loss of the dentin (n=4). After this period, the specimens were weighed until stabilization of the final mass occurred (0.001g). The solubility of each material was evaluated. ANOVA and Tukey statistical tests were performed (α=0.05). Result: BCR and MTAHP showing gain of mass in DW and mass loss in PBS (p<0.05). Conclusion: The immersion solution influenced the solubility of BCR and MTAHP using dentin tube model. The new methodological proposal could be an alternative to ISO standards for testing the solubility of bioceramic cements.
Nova proposta para avaliação da solubilidade de materiais biocerâmicos em tubos de dentina após imersão em PBS: um estudo laboratorial
Keywords: Calcarea silicata; dental materials; endodontics; physical properties